Real and Complex Singularities. - Nabarro, Ana Claudia (Contemporary Mathematics., 2016)
This volume is a collection of papers presented at the XIII International Workshop on Real and Complex Singularities, held from July 27-August 8, 2014, in São Carlos, Brazil, in honor of María del Carmen Romero Fuster's 60th birthday. The volume contains the notes from two mini-courses taught during the workshop: on intersection homology by J.-P. Brasselet, and on non-isolated hypersurface singularities and Lê cycles by D. Massey. The remaining contributions are research articles which cover topics from the foundations of singularity theory (including classification theory and invariants) to t.